Relationship between resilience and school culture with psychological well-being of school teachers - Mat Zin, Nur Izzati; Zainudin, Zaida Nor; Sulong, Rose Manisah (Human Resources Management Academic Research Society (HRMARS), 2023)
The teaching profession today is becoming increasingly challenging. This study aims to review school culture, the level of resilience and psychological well-being of teachers in primary schools. Differences in psychological well-being based on length of service and the relationship between resilience and school culture with psychological well-being were also studied. This study also identified the main factors that contribute to the psychological wellbeing of primary school teachers. Quantitative methods were used with a correlational design involving a total of 256 primary school teachers who were randomly selected from the state of Perak. The instruments used for this study are the Ryff Psychological Well-Being Scale, the Workplace Resilience Scale and the Gruenert and Vallentine Positive School Culture Scale. The research data was analyzed using SPSS software which involved descriptive and inferential analysis. The findings of the study found that resilience and school culture have a relationship with the psychological well-being of teachers in primary schools. However, only resilience is a factor for the well-being of teachers in primary schools. The findings of the study may help the education sector, especially the state education department in enacting new policies and also provide training for teachers in order to increase the resilience and psychological wellbeing of today's teachers.